Acupuncture therapy on myofascial pain syndrome: a systematic review and meta-analysis - Xiong, Jingwen; Zhou, Xuancheng; Luo, Xiufang; Gong, Xiangjin; Jiang, Lai; Luo, Qiang; Zhang, Shengke; Jiang, Chenglu; Pu, Tong; Liu, Jie; Zhang, Jun; Li, Bo; et al. (Frontiers in Neurology, 2024)
Purpose：Traditional Chinese medicine (TCM) therapies, especially acupuncture, have received increasing attention in the field of pain management. This metaanalysis evaluated the effectiveness of acupuncture in the treatment of myofascial pain syndrome. Methods: We conducted a comprehensive search across several databases -PubMed, Web of Science, Cochrane Library, WANFANG, China National Knowledge Infrastructure (CNKI), Sinomed, and the Chinese Journal of Science and Technology (VIP). Additionally, articles of studies published from the inception of these databases until November 22, 2023 , were reviewed. This systematic review and meta-analysis included all randomized controlled trials (RCTs) on acupuncture for myofascial pain syndromes without language or date restrictions. We critically assessed all outcome indicators reported in these trials. Evidence was synthesized by calculating the mean difference (MD) of symptom change. Quality of evidence was adjudicated using the Cochrane Risk of Bias tool. This study is registered with PROSPERO under registration number CRD42023484933 Results：Our analysis included 10 RCTs in which 852 patients were divided into two groups: an acupuncture group (427) and a control group (425). The results of the study showed that acupuncture was significantly more effective than the control group in treating myofascial pain syndromes, which was reflected in a greater decrease in VAS scores (MD=-1.29, 95% [-1.65,-0.94], p< 0.00001). In addition, the improvement in PRI and PPI was more pronounced in the acupuncture group (PRI: MD = -2.04, 95% [-3.76,-0.32], p=0.02) (PPI: MD = -1.03, 95% [-1.26,-0.79], p< 0.00001).compared to the control group. These results suggest that acupuncture is effective in reducing myofascial pain. It is necessary to further study the optimal acupoints and treatment time to achieve the best therapeutic effect.